A method for estimating the volume of Baltic timber products exported through the Sound and its application to Portugal, 1669–1815. Issue 3 (2nd September 2018) - Kumar, Manish
ABSTRACT: In this paper, I propose a method for estimating the volume of Baltic timber products exported through the Danish Sound, the strait separating the North Sea from the Baltic, during the early modern period. This method is based on the toll levied on the ships passing through the Sound. The main source used in this study is Sound Toll Registers Online. With the expansion of long-distance maritime trade during the early modern period, the Baltic played an important role by supplying naval stores (timber, pitch, tar, etc.) to the Western and Southern European nations. Until now exports of Baltic timber products have been analysed in terms of either the number of pieces or their weight. Both these approaches fail to shed light on the size (width, thickness, length) of timber products. On the other hand, the estimates presented in this article provide a clear picture about the size, hence the volume of the various timber products.